2017
DOI: 10.1186/s12879-017-2373-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free hemoglobin mediated oxidative stress is associated with acute kidney injury and renal replacement therapy in severe falciparum malaria: an observational study

Abstract: BackgroundIntravascular hemolysis is an intrinsic feature of severe malaria pathophysiology but the pathogenic role of cell-free hemoglobin-mediated oxidative stress in severe malaria associated acute kidney injury (AKI) is unknown.MethodsAs part of a prospective observational study, enrolment plasma cell-free hemoglobin (CFH), lipid peroxidation markers (F2-isoprostanes (F2-IsoPs) and isofurans (IsoFs)), red cell deformability, and serum creatinine were quantified in Bangladeshi patients with severe falciparu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 39 publications
7
60
0
Order By: Relevance
“…Systemic inflammation is the net result of an interplay between pro- and anti-inflammatory responses, and a shift towards a pro-inflammatory status can cause malfunctioning of the host's mitochondria in malaria, leading to organ damage [ 34 ]. The resulting oxidative stress as observed in uncomplicated malaria is known to play a role in pathogenesis [ 35 ]. For instance, lipid peroxidation and antioxidant enzyme activity associate with cholestatic jaundice in P. vivax patients [ 36 ], and oxidative stress causes hepatocyte apoptosis in murine malaria models [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation is the net result of an interplay between pro- and anti-inflammatory responses, and a shift towards a pro-inflammatory status can cause malfunctioning of the host's mitochondria in malaria, leading to organ damage [ 34 ]. The resulting oxidative stress as observed in uncomplicated malaria is known to play a role in pathogenesis [ 35 ]. For instance, lipid peroxidation and antioxidant enzyme activity associate with cholestatic jaundice in P. vivax patients [ 36 ], and oxidative stress causes hepatocyte apoptosis in murine malaria models [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine has a recognized role in maintaining the intestinal barrier function (21)(22)(23) and has a potential prognostic utility in critical illnesses (24,25). As the precursor to antioxidant cofactors, such as glutathione and NAD, low plasma glutamine levels might reduce the ability to resist the oxidative stress of malaria (26)(27)(28)(29) and other disease states. While one observational study found glutamine levels to be in the normal range among Gabonese children with severe malaria (30), low blood glutamine levels have been described in Ghanaian children with severe malaria (31) and Malawian children with cerebral malaria (32).…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with recent studies on a heme-mediated oxidative mechanism of AKI and the renoprotective effect of acetaminophen interfering with this mechanism. We recently showed that elevated plasma CFH, F 2 -IsoPs, and IsoFs are associated with in-hospital creatinine rise, hemodialysis requirement, and mortality in patients with severe malaria [ 10 ]. Acetaminophen has been shown to reduce toxic ferryl heme to ferric heme in vitro and to decrease plasma F 2 -IsoPs and improve kidney function in a rat model of rhabdomyolysis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular hemolysis is an intrinsic component of severe falciparum malaria pathophysiology [ 9 ]. Recently it was shown that increased levels of CFH, F 2 -IsoPs, and IsoFs are strongly associated with kidney dysfunction and hemodialysis requirement in adults with severe malaria [ 10 ]. Acetaminophen inhibits hemoprotein-mediated lipid peroxidation by reducing heme-ferryl radicals [ 11 ].…”
mentioning
confidence: 99%